Influence of Die Angle on Bi-2212 Wire Processing for Nuclear Fusion - JIAO Gaofeng; HAO Qingbin; XU Xiaoyan; LIU Guoqing; LIU Xueqian; JIA Jialin; ZHANG Shengnan (发电技术)
ObjectivesWith the rapid development of the steady high magnetic field, the requirements for the performance and uniformity of superconducting magnets have become increasingly stringent, resulting in the current Bi2Sr2CaCu2Ox (Bi-2212) high-temperature superconducting wires failing to meet the application requirements in terms of comprehensive performance. In order to enhance the performance and uniformity of Bi-2212 superconducting wires and achieve the preparation of wires with superior comprehensive performance, the uniform processing technology for multi-core wires is of utmost importance. Die angle is an important parameter of the wire. Therefore, the influence of different die angles on the wire processing was studied.MethodsMultiple Bi-2212 wires were prepared using the powder-in-tube method and processed with alloy drawing dies with half die angles of 3°, 7° and 14°, respectively. During the experiment, systematic investigations were conducted on the microstructure, powder hardness, and superconducting physical properties of the wires.ResultsThe wires processed with smaller die angles show higher current-carrying capabilities, especially, the current-carrying capacity of the sample with a 3° half die angle is 1.56 times that of the sample with a 14° half die angle. The Wires processed with a large die angle show core wire fractures and silver layer ruptures, leading to decreased performance, while the wires with smaller die angles maintain structural integrity. Furthermore, the choice of die angle significantly affects the smoothness of the Ag/superconductor interface, with wires processed at smaller die angles demonstrating superior interface smoothness. This further influences the texture of the superconducting filaments and the current-carrying capacity of the wires.ConclusionsSmaller half die angles help maintain the structural integrity of the multi-filament Bi-2212 wire cores and improve the current-carrying capacity by enhancing the texture. The research results provide process guidance for the preparation of high-performance Bi-2212 wires.